2018
DOI: 10.1371/journal.pone.0198159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shading and light recovery on the growth, leaf structure, and photosynthetic performance of soybean in a maize-soybean relay-strip intercropping system

Abstract: Intercropping is an important agronomic practice adopted to increase crop production and resource efficiency in areas with intensive agricultural production. Two sequential field trials were conducted in 2015–2016 to investigate the effect of shading on the morphological features, leaf structure, and photosynthetic characteristics of soybean in a maize-soybean relay-strip intercropping system. Three treatments were designed on the basis of different row configurations A1 (“50 cm + 50 cm” one row of maize and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
66
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 27 publications
11
66
0
5
Order By: Relevance
“…This increase might be due to the improved light conditions, reduced shade and optimum thermal conditions at the remaining leaves of the maize that probably increased the chlorophyll contents of maize plants (Figure ). Similarly, other researchers have argued that improved light conditions increase the chlorophyll content of soybean plants (Fan et al, ; Feng et al, ). Photosynthetic characteristics are responsive to variation in LAI caused by various leaf excision treatments (T. Liu et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 75%
“…This increase might be due to the improved light conditions, reduced shade and optimum thermal conditions at the remaining leaves of the maize that probably increased the chlorophyll contents of maize plants (Figure ). Similarly, other researchers have argued that improved light conditions increase the chlorophyll content of soybean plants (Fan et al, ; Feng et al, ). Photosynthetic characteristics are responsive to variation in LAI caused by various leaf excision treatments (T. Liu et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 75%
“…Leaves of crops are sensitive to the light environment and photosynthetic capacity is generally decreased by shading (Fan et al., ). As a cereal and a C 4 crop, maize is highly efficient at light interception and utilization (Omoto, Taniguchi, & Miyake, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, past studies have confirmed the adverse impacts of shading conditions on soybean morphology (Khalid et al, 2019;Raza, Feng, Iqbal, Ahmed, et al, 2019), physiology (Feng et al, 2018), and dry-matter accumulation (Ahmed et al, 2018;Yang et al, 2014). However, after maize harvesting in MSR, soybean exhibit strong recovery growth (Wu et al, 2016), and the competition for available resources with maize is compensated from the vegetative stage to the flowering stage (Fan et al, 2018). At the reproductive stage, soybean in MSR has better access to available resources compared to sole soybean plants, especially for light and nutrients .…”
Section: Introductionmentioning
confidence: 91%
“…In MSR, maize produces higher seed yield due to optimum growth and an edge row-effect, and in some studies, relay-cropped maize produced higher seed yield as compared to maize yield in sole cropping systems (Chen et al, 2017;Raza, Feng, Khalid, Iqbal, Meraj, et al, 2019;Yang et al, 2017). However, soybean in MSR produced lower crop yield than sole soybean because it is planted two months after maize sowing, and the severe competition for available resources with maize plants reduces the initial growth of soybean plants (Fan et al, 2018). Moreover, past studies have confirmed the adverse impacts of shading conditions on soybean morphology (Khalid et al, 2019;Raza, Feng, Iqbal, Ahmed, et al, 2019), physiology (Feng et al, 2018), and dry-matter accumulation (Ahmed et al, 2018;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%